ANALISIS DAN EVALUASI MANAJEMEN RITEL BERDASARKAN KERANGKA KERJA COBIT 5 - Devi Yurisca Bernanda; Johanes Fernandes Andry (Infotech: Journal of Technology Information, 2025)
Many retail stores still face challenges in data management, services, and risk control, impacting operational effectiveness and competitiveness. The COBIT 5 framework offers a comprehensive approach to assessing, controlling, and improving information technology governance to align with business objectives. The application of COBIT 5 in the retail sector is relatively rare, despite the fact that this sector has different operational dynamics than other industries. Therefore, this study focuses on the analysis and evaluation of retail management using the COBIT 5 framework to identify the level of governance maturity and provide applicable improvement recommendations. The research method stages include: (a) literature review on COBIT 5 and IT governance practices in the retail industry; (b) identification of COBIT 5 domains relevant to the retail management context; (c) data collection through interviews, observations, and questionnaires with retail management and staff; (d) maturity level analysis based on the COBIT 5 framework; and (e) preparation of recommendations for improving retail management based on IT governance. The retail management evaluation in this study uses the COBIT 5 framework that focuses on the Align, Plan, and Organize (APO) domains, namely APO11 Manage Quality and APO12 Manage Risk. The assessment of the APO11 and APO12 capability levels was conducted to evaluate the implementation of quality management in the division. The results of the quality management measurement in this division reached level 2 (Manage Processes). Recommendations have been compiled that can be implemented by this division so that the APO11 and APO12 capability levels reach the desired level, namely level 3 (defined process), so that they can support the company's business processes in terms of information technology.